Homeschooling Model Management (A Study at Anugrah Bangsa Package A Homeschooling Semarang) - Sandi, Puput Ari; Sutarto, Joko; Yusuf, Amin (Journal of Primary Education, 2018)
This research was a qualitative research with case study approach. This study has purpose to find out the detail of the implementation of management education in homeschooling Package A Anugrah Bangsa Semarang. This study discussed in depth, covering the planning, implementation and evaluation of the educational programs of homeschooling package A Anugrah Bangsa Semarang. The research subject were the chairman of community learning centers (PKBM) Anugrah Bangsa Foundation Semarang, Principal, Coordinator of package A and tutors of package A. The data collection techniques was done by using in-depth interviews, observation, and documentation. The results showed that the planning of homeschooling package A Anugrah Bangsa Semarang was done by identifying the learners, tutors, infrastructure, financing, as well as class grouping. Homeschooling package A Anugrah Bangsa Semarang conducts learning by capturing method. The evaluation of Homeschooling package A Anugrah Bangsa Semarang has featured program of giving ecofarming based live skills.